A babysitter's guide to monster hunting - Ballarini, Joe (Ballarini, Joe. Babysitter's guide to monster hunting (Series), 2019)
When Kelly loses a little boy to monsters who live under his bed during her first babysitting job, she learns about a secret society of babysitters who fight monsters.